Systematic Literature Review: Analisis Strategi Antisipasi Perubahan Masa Depan - Mochammad Najibulloh; Malida Nur Izzatul Mursyidah; Khoirul Anwar; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Future changes marked by digital technology development, globalization, and social transformation have significantly influenced the field of education. These conditions require educational institutions to develop anticipatory strategies in order to remain relevant to the needs of the modern era. This study aims to analyze strategies for anticipating future changes in education and to examine the role of Islamic Religious Education in facing modern developments. This research used a literature review method with a Systematic Literature Review (SLR) approach. The main data sources consisted of six scientific journal articles published between 2022 and 2024, which were selected through Google Scholar and national journals. The data were analyzed descriptively and qualitatively through the stages of identification, selection, evaluation, and thematic synthesis. The findings show that anticipatory strategies in education can be implemented through curriculum development, teacher competency improvement, digital technology utilization, change management, and the strengthening of 21st-century skills. In addition, Islamic Religious Education has a strategic role in shaping students’ character, morality, and spirituality so that they can adapt to modern developments without neglecting Islamic values. The results of this study imply that educational institutions and Islamic Religious Education teachers need to develop adaptive, innovative, and value-based learning strategies to prepare students for future challenges.